Implementation of the Stimulus-Organism-Response (S-O-R) Model in Analysing Impulse Buying of Fashion Products on Shopee Live Streaming Shopping - Suyono, Fatasya; Palupi, Ghea Sekar (Universitas Negeri Surabaya, 2026)
E-commerce is now an important part of the lives of Indonesians, fuelled by the development of technology and smartphones. Recent studies have identified live streaming as a key trend in e-commerce, with particular reference to its use in increasing interaction between sellers and buyers. The most widely used platform for live streaming shopping is Shopee Live. This research focuses on fashion products, which show high purchase rates through Shopee Live. The change in consumer behaviour, from relying on product descriptions to direct interaction with sellers, raises questions about the factors that drive impulse purchases in this context. The present study has been designed to identify the factors that influence the impulse purchase of fashion products on Shopee Live. To this end, the Stimulus-Organism-Response framework has been adopted. Data was collected through a survey of respondents who had made fashion purchases on Shopee Live. The data were analysed using the PLS-SEM method with SmartPLS 3.0 software. The results showed that the variables of attractiveness, trustworthiness, and expertise have a positive and significant effect on perceived enjoyment, while product usefulness, purchase convenience, and product price have a positive influence on perceived usefulness. In addition, it was found that perceived usefulness and perceived enjoyment contribute significantly to the impulse purchase of fashion products.